Influence of probionts on the gut microbial diversity in pearl spot, Etroplus suratensis (Bloch) - Immanuel, G; Menenthira, V; Prema, P; Palavesam, A (Indian Journal of Fisheries, 2011)
Qualitative and quantitative aspects of bacterial population in the gut of Etroplussuratensis collected from wild, following one day starvation and also in fishesfed with probionts supplemented diets such as Lactobacillus acidophilus (FeedA) and Yeast - Saccharomyces cervisiae (Feed B) were studied. The total aerobicheterotrophic bacterial counts in gut contents of wild and one day starved fishwere 31.0 x 106 and 22.6 x 106 CFU / ml. Similarly in fishes fed with probiontssupplemented diets and control diet (Feed C) cultured for 15 and 30 days, thebacterial counts registered were 26.40 x 106, 22.9 x 106 and 29.9x 106 CFU / mland 28.2x 106, 27.6x 106 and 22.3 x 106 CFU/ml during 15th and 30th days ofexperiment in fish fed with L. acidophilus, Yeast, S. cervisiae and control dietsrespectively. Totally eleven bacterial genera were identified in all the gut samplesand among these, Pseudomonas, Bacillus, Micrococcus and Alcaligenes weredominant during 30th day of the experiment.